SUSTAINABILITY AND OCCUPATIONAL SAFETY: IMPLEMENTING SUSTAINABLE PRACTICES IN THE WORKPLACE TO REDUCE ENVIRONMENTAL IMPACT AND IMPROVE SAFETY - de Melo, Sheila Silva (Revista Sistemática, 2022)
The integration of sustainability and occupational health and safety has gained increasing attention in organizational management as companies seek to reduce environmental impacts while ensuring safe and healthy working conditions. This article examines how sustainable practices implemented in the workplace can simultaneously enhance environmental performance and improve occupational safety outcomes. By adopting preventive approaches, efficient resource management, and integrated management systems, organizations can reduce exposure to environmental and occupational hazards, promote employee well-being, and strengthen long-term organizational resilience. The analysis highlights the role of international standards, employee engagement, and proactive risk management in aligning sustainability objectives with occupational safety strategies. The findings suggest that integrating environmental responsibility and worker protection contributes not only to regulatory compliance but also to operational efficiency, improved safety performance, and enhanced corporate reputation.